(2x-3)^2(x-3)=(2x+3)(x-3)^2

(2x-3)^2(x-3)=(2x+3)(x-3)^2
Гость
Ответ(ы) на вопрос:
Гость
[latex](2x-3)^2(x-3)=(2x+3)(x-3)^2[/latex] [latex](2x-3)^2*(x-3)-(2x+3)(x-3)*(x-3)=0[/latex] [latex][(2x-3)^2-(2x+3)(x-3)]*(x-3)=0[/latex] [latex](2x-3)^2-(2x+3)(x-3)=0,or,x-3=0[/latex] [latex](2x)^2-3*2x*2+3^2-(2x^2-6x+3x-9)=0,or,x=3[/latex] [latex]4x^2-12x+9-(2x^2-3x-9)=0,or,x=3[/latex] [latex]4x^2-12x+9-2x^2+3x+9=0,or,x=3[/latex] [latex]2x^2-9x+18=0,or,x=3[/latex] У квадратного уравнения действительных корней нету: [latex]D=(-9)^2-4*2*18=9*9-8*18<0[/latex] Ответ: [latex]3[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы